Mindfulness, abertura para experiência e depressão: um estudo utilizando aplicativo móvel - Tavares, Joel Jonathan Carvalho (2022)
In recent years, cases of depression have increased worldwide. One of the aspects that can predict depression is related to personality traits. Fortunately, there are several pharmacological and non-pharmacological treatments for depression. An example is the mindfulness practice, which has shown effective results as a therapeutic resource for managing depressive symptoms. The use of technology for remote healthcare may hold promise, especially in developing countries. Digital phenotypes are sources of objective information collected remotely. The first part of this research aimed to investigate the possible mediating effect of the five facets of mindfulness on Openness to Fantasy (OF) and depression. The purpose of the second part of the study was to explore the relationship between digital phenotypes, depression, and Openness to Experience (OE) traits. In the first study, 153 individuals aged between 18 and 65 participated in answering an electronic form. We performed simple and multiple mediation analyses between the facets of mindfulness, fantasy, and depression. We conducted a second study with a cross-sectional and correlational design, in which 364 adults aged between 18 and 68 participated. We collected the data over the internet through an APP. Based on the objectives proposed in our studies, the results of the first paper revealed preliminary evidence that the fantasy factor is related to depressive symptoms. But the mindfulness trait had a mediating role in reducing the direct effect of the fantasy and depression relationship. The non-judgmental facet of mindfulness played a predominant role in this mediating force, which suggests that the act of not judging the internal experience may be a protective factor for depression in people with a higher rate of OF. Results from the second study indicated that participants with shorter response times had significantly higher rates of depression and fantasy. Our studies are limited to observing the relationship between variables, and investigating the importance of mindfulness facets as protective factors against depression. Also, we look for early evidence of digital phenotypes as biomarkers for online mental health care. Based on the results found and discussed in chapters II and III, we concluded that the mindfulness trait, especially the non-judgmental facet, is considered the principal individual attribute for the protection of mental health, which makes it relevant to promote its practice, especially as a tool to promote online mental health care. Another relevant result in our studies is the importance of digital phenotypes as biomarkers for assessing and tracking aspects of people's health in their natural environment, using technological tools that allow the collection of clinical information in an objective and less biased way.